2010
DOI: 10.1111/j.1532-849x.2010.00625.x
|View full text |Cite
|
Sign up to set email alerts
|

Taper of Full-Veneer Crown Preparations by Dental Students at the University of the West Indies

Abstract: This study shows that although the taper achieved by dental students in the University of the West Indies when preparing teeth for full-veneer crowns was outside the ideal range of 4° to 14°, it is comparable to those achieved by dental students in other schools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
1
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(59 citation statements)
references
References 19 publications
5
47
1
6
Order By: Relevance
“…The results of this experiment were published by Rafeek et al, (2010). There were no undercuts detected on any of the laboratory specimens as compared to the clinical specimens where 12.5% were undercut.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…The results of this experiment were published by Rafeek et al, (2010). There were no undercuts detected on any of the laboratory specimens as compared to the clinical specimens where 12.5% were undercut.…”
Section: Resultssupporting
confidence: 68%
“…Although dimensional measurements have been widely applied in dental research, for some of the measurements, such as taper angle measurement, a consensus has been demonstrated (Noonan & Goldfogel, 1991;Sato et al, 1998;Patel et al, 2005;Ayad et al, 2005;Mack, 1980;Rafeek et al, 2006Rafeek et al, , 2010. In other areas, such as tooth wear measurements (Zhou and Zheng, 2008;Pintado MR et al, 2000;Mitchell and Chadwick, 1998) this has not been the case.…”
Section: Standards Around the Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Mack (21) observed that a minimal taper of 12 degrees was necessary to ensure the absence of undercuts. The widely recommended 12°TOC has been Copyright shown to be difficult to achieve for many dental students (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…Quality of tooth preparation is influenced by occlusal reduction, axial reduction, occlusal convergence, aspect of cervical preparation and axial walls. There are many studies that analyse the quality of tooth preparation for coverage crowns done by students [3][4][5], dentists [6], residents [5] or specialists [7]. Majority of these evaluates TOC, neglecting other aspects of preparation, which are most commonly errors denounced by dental laboratories [8].…”
Section: Introductionmentioning
confidence: 99%